Management Of Reba Rituals In The Bhajava Ethnic Farmer Community, Java Meze Sub-District, Bajawa District, Ngada Regency - Nong Hoban; Bonaventura R. Seto Se (Institute of Computer Science (IOCS), 2022)
The problem raised in this study is how the procedure of reba ritual in the Bhajawa ethnic farming community, Jawa Meze Village, Bajawa District, Ngada Regency. The purpose of this study was to determine the management of the reba ritual in the Bhajawa ethnic farming community, Jawa Meze Village, Bajawa District, Ngada Regency. The research method used is qualitative research. Data collection techniques are interviews, observation, and documentation. Data analysis techniques are as follows: data reduction, data presentation, and drawing conclusions. The results showed that the form of reba ritual management has been patterned in the Bhajawa ethnic tradition which is a total unity, implemented in a tradition that is oriented to the past and has a great influence. The procedures for the reba ritual are as follows: Wasi Loka Lanu (cleaning the offerings), Bui Loka (giving dishes) accompanied by a request to the ancestors and the Supreme Wujut, Kobe Dheke (opening night of the reba) starting with the slaughter of the sacrificial animal accompanied by a request to the ancestors and the highest Wujut and lowering the bhoka and su'a from the storage area, (the storage area above the body eye), Kobhe Dhoy (closing night). Kobe Dhoy began with the slaughter of the sacrificial animal accompanied by a request to the ancestors and the Supreme Wujut. This opportunity is usually used to evaluate and plan ana woe (tribal) activities for a year.